Cellular discrimination using in vitro Raman micro spectroscopy: the role of the nucleolus1. Issue 17 (7th September 2015) - Farhane, Z.; Bonnier, F.; Casey, A.; Maguire, A.; O'Neill, L.; Byrne, H. J.
<x xml:space="preserve">Abstract</x> Raman micro spectroscopy is employed to discriminate between cell lines. Results show the importance of the nuclear sub-cellular organelle, the nucleoli, to differentiate between cancer cell lines with high specificity and sensitivity.